METHOD OF ASSESSING THE INFLUENCE OF WASHING ON PHYSICO-MECHANICAL INDICATORS OF FABRIC - RIPKA, GALYNA; MAZNIEV, IEVGEN; TIELUSHKINA, OLHA; ZASORNOVA, IRYNA (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article considers an improved method of comprehensive assessment of the impact of washing at home on the physical and mechanical properties of textile materials intended for the manufacture of children’s casual wear. In developing the methodological basis for assessing the change in the properties of fabrics from washing, we used the results of our own observations, which allowed us to analyze the operating conditions of preschool children’s clothing, activities and characteristic movements of children on playgrounds, identify key factors of destruction of products. features, topography of wear, frequency of cleaning from dirt, method of drying, etc. Thus, it can be argued that the shrinkage of fibrous systems depends on a sufficient number of factors that can affect simultaneously and comprehensively, and therefore this process should be classified as multifactorial and difficult to study, as the evaluation method used today is insufficient informative. The maximum allowable norms of such indicators as breaking characteristics up to (-15%) have been established; air permeability coefficient up to (-15%); abrasion resistance on the plane up to (-30%); thickness up to (+20%). The recommended method has been tested experimentally. Evaluation of changes in physical and mechanical characteristics of samples from the impact of repeated processing in the washing bath of a new recipe, close to home, was performed after each wash cycle using informative indicators such as breaking force based on Po, (N) air permeability coefficients Kp (dm3/m2·s) resistance of samples to abrasion in the plane Cs (cycles) and its thickness L (mm). The obtained results show the dependence of all indicators without exception on the number of washing cycles in soap and soda solution, with such as bursting loads of samples, their resistance to abrasion on the plane and air permeability decreases, and thickness increases compared to initial characteristics. The textile material should be considered resistant to the number of washing cycles in the soap and soda solution, which led to a change in at least one of the four criteria to the specified maximum allowable values.